Ecology of the Verreaux's eagle Aquila verreauxii in natural and agriculturally transformed habitats in South Africa - Murgatroyd, Sarah Megan (Percy FitzPatrick Institute of African Ornithology, 2016)
Agricultural transformation generally has a negative impact on biodiversity. Owing to landscape fragmentation and reduced prey availability, predators that inhabit transformed areas are usually forced to increase hunting effort or diversify their diet and this can have negative consequences for fitness or demographic parameters. Agricultural landscapes are therefore rarely considered important in the conservation of top predators. The Verreaux's eagle Aquila verreauxii has experienced loss of natural habitat due to agricultural transformation through much of its range. Despite the conspicuous nature and widespread distribution of Verreaux's eagles in sub- Saharan Africa, there is a paucity of information on the mechanism behind the recently observed population declines of this species, which have resulted in the recent re-classification as "Vulnerable" (from "Least Concern") in South Africa. This thesis aims to explore how land transformation influences changes in several key ecological components and demographic parameters, namely breeding performance, diet and movement ecology. In this thesis, I study two geographically adjacent populations of Verreaux's eagles; one located in a natural area (Cederberg) and one in an agriculturally transformed area (Sandveld), in the Western Cape Province, South Africa, from 2011-2014. I investigate the breeding performance of the two populations. In contrast to what was anticipated I found that breeding productivity was 2.7 times greater in the agricultural than in the natural area. Population modelling suggested that in isolation the Cederberg population is unlikely to be self-sustaining, whereas the eagles breeding in the Sandveld region are likely to be acting as a source population. However, I did not have any information about juvenile or adult survival in either area. Contrasting survival rates could distort these results and are in need of further research. Verreaux's eagles are generally regarded as dietary specialists. I therefore investigated the diet composition of eagles in the two study areas as a proxy to better understand prey availability and to look for evidence of behavioural flexibility to different availability of prey resources. The relationship between diet breadth and breeding performance was explored locally and regionally using data from previous studies. Eagles in the Sandveld were found to have a more diverse diet than eagles in the Cederberg, which rely on their traditional prey, rock hyrax Procavia capensis. Theory on specialist predators assumes that diet diversification will cause reduced breeding performance. In particular, individuals within a species with more diverse diets due to reduced availability of primary prey species can display reduced breeding performance. In direct contrast to this, eagles with broad diet did not exhibit trends for reduced breeding performance, both locally and across southern Africa.